Foetal akinesia deformation sequence; a rare lethal entity- A case report - Shafqat, Gulnaz; Fatima, Kulsoom; Hanif, Farida (Journal of the Pakistan Medical Association, 2023)
Foetal akinesia deformation sequence (FADS) represents a group of disorders resulting from absent or diminished in utero foetal mobility. The aetiology is multifactorial, including genetic, environmental, maternal, and foetal causes. The absence of foetal movements leading to multiple joint contractures, pulmonary hypoplasia, and intrauterine growth restriction are the key features of foetal akinesia deformation sequence. Herein we describe the case of a 30-year-old gravida 4 (para 2+1) who came for foetal ultrasound at 28 weeks of gestation due to decreased foetal movements. Ultrasound showed features of FADS with fixed flexed position of foetal limbs, pulmonary hypoplasia, polyhydramnios, and intrauterine growth restriction. The timely use of ultrasound enables early detection of these cases and aids in appropriate counselling and management. Keywords: Foetal arthrogryposis, antenatal, foetal akinesia, ultrasound.